2004
DOI: 10.1038/labinvest.3700027
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia increases Hsp90 binding to eNOS via PI3K-Akt in porcine coronary artery endothelium

Abstract: This study examines the molecular mechanisms by which hypoxia regulates phosphorylated endothelial nitric oxide synthase (eNOS) activity and NO production in porcine coronary artery endothelial cells (PCAEC). Exposure to hypoxia (pO 2 ¼ 10 mmHg) for periods up to 3 h resulted in a time-dependent increase in eNOS protein expression and an early (15 min) and sustained increase in eNOS phosphorylation at Ser-1177. Exposure to hypoxia for 30 min led to a doubling in eNOS activity (control ¼ 6.274.4 vs hypoxia ¼ 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 47 publications
3
49
0
Order By: Relevance
“…Chen and Meyrick28 found that acute hypoxia stimulated Hsp90 binding to eNOS and activation of the PI3–Akt pathway resulting in increased eNOS phosphorylation. They suggested that this may be a mechanism whereby eNOS activity and subsequent NO production is upregulated in hypoxic coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Chen and Meyrick28 found that acute hypoxia stimulated Hsp90 binding to eNOS and activation of the PI3–Akt pathway resulting in increased eNOS phosphorylation. They suggested that this may be a mechanism whereby eNOS activity and subsequent NO production is upregulated in hypoxic coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…For hypoxia studies [24], the cells were exposed to normoxia (PO 2 = 160 mmHg) or hypoxia (PO 2 < 10 mmHg) for various time periods with basic medium containing 0.1% FBS in normal incubator or an air-tight chamber (MIC-101, Billups-Rothenberg, Inc.) flushed with 95% N 2 /5% CO 2 . The cells were then immediately harvested for western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…HIF-1 increases the expression of endothelial nitric oxide synthase (eNOS) and the extent of eNOS phosphorylation (Chen and Meyrick, 2004; Dedkova et al , 2004; Shi et al , 2002), HIF-1 suppresses SDHB (Dahia et al , 2005), stimulates expression of PDK and LDHA (Firth et al , 1995; Kim et al , 2006; Papandreou et al , 2006; Semenza et al , 1996) and is involved in the regulation of mitochondrial mass via inhibition of biogenesis (Zhang et al , 2007) and the stimulation of mitochondrial autophagy (Zhang et al , 2008). …”
Section: Hypoxia and Hif-1 Mediation Of Metabolic Reprogrammingmentioning
confidence: 99%